A randomised trial of bilateral erector spinae plane block vs. no block for thoracolumbar decompressive spinal surgery. (20th April 2021) - Finnerty, D.; Ní Eochagáin, A.; Ahmed, M.; Poynton, A.; Butler, J. S.; Buggy, D. J.
Summary: Major spinal surgery causes significant postoperative pain. We tested the efficacy and safety of bilateral erector spinae block on quality of recovery and pain after thoracolumbar decompression. We randomly allocated 60 adults to standard care or erector spinae block. Erector spinae block improved the mean (SD) quality of recovery‐15 score at 24 postoperative hours, from 119 (20) to 132 (14), an increase (95%CI) of 13 (4–22), p = 0.0044. Median (IQR [range]) comprehensive complication index was 1 (0–3 [0–5]) in the control group vs. 1 (0–1 [0–4]) after block, p = 0.4. Erector spinae block reduced mean (SD) area under the curve pain during the first 24 postoperative hours: at rest, from 78 (49) to 50 (39), p = 0.018; and on sitting, from 125 (51) to 91 (50), p = 0.009. The cumulative mean (SD) oxycodone consumption to 24 h was 27 (18) mg in the control group and 19 (26) mg after block, p = 0.20. In conclusion, erector spinae block improved recovery and reduced pain for 24 h after thoracolumbar decompression surgery. 요약: 주요 척추 수술은 수술 후 상당한 통증을 유발한다. 저자들 은 흉요추 감압 후 회복의 질과 통증에 대한 양측 척추 기립 면 차단의 효능과 안전성을 검사하였다. 저자들은 60명의 성 인을 표준 치료 또는 척추 기립면 차단에 무작위로 할당하였 다. 척추 기립면 차단은 수술 후 24시간 시점에서 회복의 질‐15 점수의 평균(표준편차)을 119 (20)에서 132 (14)로 향상 시켰고, 이는 13 (95% CI 4‐22) 만큼의 증가, p = 0.0044였다. 종합 합병증 지수의 중앙값(사분위간[범위])은 대조군 1 (0‐3 [0‐5]) 대비 차단 후에서 1 (0‐1 [0‐4]), p = 0.4였다. 척추 기립 면 차단은 수술 후 처음 24시간 동안 통증 곡선 아래 평균(표 준편차)의 면적을 감소시켰다. 휴식 시 78 (49)에서 50 (39)까 지, p = 0.018이었고; 앉아 있을 때는 125 (51)에서 91 (50)까지, p = 0.009였다. 24시간까지 옥시코돈 소비의 누적 평균(표준편 차)은 대조군에서 27 (18) mg, 차단 후에서 19 (26) mg, p = 0.20이었다. 결론적으로, 척추 기립면 차단은 흉요추 감압 수 술 후 24시간 동안 회복을 개선하고 통증을 감소시켰다.